Serum Iron Level in the First Trimester of Pregnancy Among Women Visiting a Tertiary Care Hospital in Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Iron plays a vital role in the development of fetus. Requirements of nutrition are increased during pregnancy for proper fetal growth and development along with the change in maternal metabolism. Thus the study was undertaken to assess hemoglobin and serum iron level in the first trimester of pregnancy with aim to focus the needs for a sustainable strategy to improve maternal and fetal micronutrition to prevent the adverse pregnancy outcome.  Materials and methods: This study was a hospital based cross sectional observational study comprising 100 pregnant women who were recruited during their first antenatal visit in the first trimester of pregnancy, while attending the Outdoor of Gynaecology and Obstetrics, Chittagong Medical College Hospital and 50 non-pregnant women as control. Serum iron and hemoglobin level were evaluated in the Department of Biochemistry, Chittagong Medical College.      Results: In this study, of 100 cases, anaemia was detected (Hb